The Frontier Myth in U.S. Offshore Wind Energy Communication - Hernandez, Nicolas C.; Horton, Cristi C.; Endres, Danielle; Peterson, Tarla Rai (Frontiers in Communication, 2019)
Increased penetration of low-carbon energy technologies, such as wind and solar, into the U.S. energy system has the potential to reduce greenhouse gas emissions, facilitate transmission of energy to remote regions, and increase opportunities for public participation in energy system change. It also offers a window of opportunity to observe the social dynamics of rapid socio-technical system change. Studying internal, yet informal, communication among energy professionals enables communication researchers to probe processes and practices of identity composition, which may, in turn, suggest opportunities to shift the relationship between energy professionals and energy consumers away from alienation and toward consubstantiation. With this goal in mind, we analyzed communication among U.S. offshore wind professionals—specifically energy scientists and engineers—at professional conferences. Textual analysis of conference presentations and ethnographic interviews indicates that scientists and engineers working with the nascent U.S. offshore wind industry are composing an identity inspired by the frontier myth. We suggest that these evocations of the frontier myth might be strategically used to cultivate consubstantiality between technically-oriented energy professionals and publics. Awareness of a common connection to frontier myth may contribute to public engagement with offshore wind energy specifically, and more generally, with low-carbon energy technologies.